دراسة استقصائية حول بعض أحرف الجر الإنجليزية ومعانيها في اللغة العربية - عيبلو, Adel (مجلة الاصالة, 2025)
This study is an attempt to investigate the use of the three English prepositions, of, from, and for, and identify the Arabic meanings of these prepositions. A good number of sentences including the three English prepositions of, from, and for were investigated and translated into Arabic for the sake of identifying the possible Arabic meanings of each preposition. The study reveals that each of the three English prepositions (of, from, for) has a number of Arabic meanings. The English preposition of has a good number of Arabic meanings. It has seven meanings in Arabic which are: (min) (( ,)مانala) (( ,)علاىbi) ( ,)لli (( ,)لan) ( ,)عانno equivalent Arabic meaning (0), and (fi) ( ).يايThe second preposition from has only three Arabic meanings – (an) (( ,)عنmin) ( ,)مانand (bi) ( ,)لwhile the preposition for has the highest number (10) of Arabic meanings. They are: (an) (),عان (bi) (( ),لala) (( ),علاىmin) ( ),مانno equivalent Arabic meaning (0), (maa) (( ,)معli) (( ),لbisabab) (،( ),بسبbadalan min) ( ),بد منand (munthu) ().من The researcher concluded the study with some recommendations and suggestions on learning prepositions in English. These suggestions are aimed to help the Arab learners of English when learning these prepositions. It can also help the teachers of English when they teach prepositions.